Mucoadhesive Delivery System : A Smart way to Improve Bioavailability of Poorly Water-Soluble Drugs - Nirmala Sunil Yewale,; Mrs. Trusha Shangrapawar,; Dr. Ashok Bhosale, (International Journal of Scientific Research in Science and Technology, 2024)
The Conventional Oral Administration Of Many Poorly Soluble Drugs Exhibits Poorly Oral Bioavailability- Oral Mucosa Has Been Recognized As A Potential Site For The Delivery Of Therapeutic Compounds. The Mucoadhesive Formulation Can Adhere To The Mucosal Membrane Through Various Interaction Mechanisms And Enhance The Retention And Permeability Of Bioactive Compounds. Absorption Of Bioactive Compounds From The Mucosa Can Improve Bioavailability, As This Route Bypasses The Hepatic First-Pass Metabolism And Transit Through The Gastrointestinal Tract. The Mucosal Administration Is Convenient, Simple To Access, And Reported For Increasing The Bioactive Concentration In Plasma. Many Mucoadhesive Polymers, Emulsifiers, Thickeners Used For The Pharmaceutical Formulation Are Accepted In The Pharmaceutical Sector. Introducing Mucoadhesive Formulations Specific To The Poorly Water Soluble Drug Sector Will Be A Game-Changer As We Are Still Looking For Different Ways To Improve The Bioavailability Of Many Bioactive Compounds. This Article Describes The Overview Of Oral Mucosa, The Concept Of Mucoadhesion And Related Theories, And Different Techniques Of Mucoadhesive Formulations. Finally The Classification Of Mucoadhesive Polymers And The Mucoadhesive Systems Designed For The Effective Delivery Of Active Pharmaceutical Compound Are Presented.
Keywords: Bioavailability; Hepatic First Pass Metabolism; Polymers; Emulsifiers